2009
DOI: 10.1111/j.1523-1739.2009.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Consequences of Genetic Variation in Bark Characteristics within a Foundation Tree Species

Abstract: The developing field of community genetics has the potential to broaden the contribution of genetics to conservation biology by demonstrating that genetic variation within foundation plant species can act to structure associated communities of microorganisms, invertebrates, and vertebrates. We assessed the biodiversity consequences of natural patterns of intraspecific genetic variation within the widely distributed Australian forest tree, Eucalyptus globulus. We assessed genetic variation among geographic race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 47 publications
(67 reference statements)
2
25
1
Order By: Relevance
“…This pattern is consistent with other community genetic studies where the genotype of the dominant species influences both the presence and abundance of species in the plantassociated community (e.g. Johnson and Agrawal, 2005;Johnson et al, 2006;Whitham et al, 2003Whitham et al, , 2006, see also Barbour et al, 2009).…”
Section: Intraspecific Competitionsupporting
confidence: 88%
“…This pattern is consistent with other community genetic studies where the genotype of the dominant species influences both the presence and abundance of species in the plantassociated community (e.g. Johnson and Agrawal, 2005;Johnson et al, 2006;Whitham et al, 2003Whitham et al, , 2006, see also Barbour et al, 2009).…”
Section: Intraspecific Competitionsupporting
confidence: 88%
“…Within temperate ecosystems, genetic variation within a dominant plant species can influence the structure of the associated invertebrate [8][9][10][11][12][13][14][15][16][17], plant [18], endophytic fungi [19] and vertebrate [20,21] communities. An important factor in these interactions has been found to be plant biochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Barbour et al [66,67] examined the effects of genetic variation in Eucalyptus globulus on dependent biodiversity. They studied 160 trees representing eight races in a 15-year-old common garden, and showed that genetic composition of trees affects species occurrence and composition of a number of other groups of organisms including arthropods, fungi, snails and spiders, not only on the living trees but also in the associated litter.…”
Section: Box 3 Genetic Contamination Of Eucalypts In Australiamentioning
confidence: 99%